Analysis of Influential Factors on Postnatal Care Utilization: A Community-based Cross-sectional Study in Kwadaso Municipality, Ghana - Owusu, Sarah Boafowaa; Bonney, Richard Abeiku; Safo, Kwame Sarkodie; Abudey, Samuel; Adu, Randolph Baah; Dassah, Edward Tieru (Journal of Maternal and Child Health, 2024)
Background: Postnatal care is central to maternal well-being as it averts cognitive complications and illnesses that come from childbirth. Non-utilization of postnatal care hinders initiatives aimed at improving maternal morbidity and mortality because postnatal care is an essential component of those initiatives. This study sought to determine factors associated with the utilization of postnatal care services among mothers in Kwadaso Municipality. Subjects and Method: Community-based cross-sectional study to assess the factors associated with utilization of postnatal care services among mothers in Kwadaso Municipality. A multistage sampling technique was used to recruit 568 women for the study. The dependent variable was mothers' utilization of postnatal care (PNC). The independent variable was demographic characteristics of mothers, socio-economic status, educational level, accessibility to healthcare facilities, knowledge of PNC Services, and awareness of PNC services. The data were collected using a structured questionnaire, the data obtained were analyzed using STATA version 14.0, and the variables were analyzed using the chi-square test and multiple logistic regression and p=0.050 was considered statistically significant. Results: The mean age was 20-25 years 22.4 (SD=3.7 years) and 55.5% were married. The level of knowledge of the mothers on postnatal care services was 71.8% and 82.3% of the subjects knew postnatal period is more dangerous to the lives of mothers and their babies. The unadjusted odds of women who were married (OR= 2.11; 95% CI= 0.86 to 7.46; p=0.042), with two children (OR=4.17; 95% CI= 0.03 to 5.30; p= 0.025), earned GHC 500.00 monthly (OR= 3.47; 95% CI= 0.26 to 5.73; p=0.038), or delivered at the hospital (OR= 3.18= 95%CI= 0.02 to 8.06; p=0.014) were statistically significantly higher in women who were not married, had more than or less than four children, earned less than GHC 500.00 or delivered at other places aside the hospital. Conclusion: This study contributes to the ongoing discourse on maternal health and underscores the importance of evidence-based interventions to improve the health and well-being of mothers and infants.